Corema album archaeobotanical remains in western Mediterranean basin. Assessing fruit consumption during Upper Palaeolithic in Cova de les Cendres (Alicante, Spain). (1st March 2019) - Martínez-Varea, Carmen M.; Ferrer-Gallego, P. Pablo; Raigón, M Dolores; Badal, Ernestina; Ferrando-Pardo, Inmaculada; Laguna, Emilio; Real, Cristina; Roman, Dídac; Villaverde, Valentín
Abstract: Information about plant gathering by Palaeolithic hunter-gatherers in Europe is scarce because of the problems of preservation of plant remains in archaeological sites and due to the lack of application of archaebotanical analysis in many of them. Botanical macroremains –wood charcoal, seeds, fruits, leaves, etc. - provide information not only about palaeoeconomy of hunter-gatherers, but also about climate, landscape and vegetation dynamics. In Gravettian and Solutrean levels of Cova de les Cendres (Alicante, Spain), Corema album pyrenes ( Empetraceae or crowberries family) have been identified. On the contrary, wood charcoal of this species has not been documented among the remains of firewood. This differential presence of plant organs, together with the nutritional value of its fruits, which is presented here, make us hypothesize the systematic gathering of C. album fruits for human consumption. They have a high content in vitamin C, as well as potassium, magnesium and copper. Corema album ( camariña ) is a unique species, nowadays in danger of extinction. Its main population is located on the Atlantic coast of Iberian Peninsula, but in 1996 a small population was discovered on the Mediterranean Iberian coast (Benidorm, Spain). Archaeobotanical data from Cova de les Cendres (Teulada-Moraira, Spain) presented here point to a larger population of camariña during Upper Palaeolithic on the coast of Alicante. The harsh climatic conditions of the Last Glacial Maximum during Solutrean period, with colder temperatures and aridity increase, could explain the reduction of the presence of C. album remains until its absence in Magdalenian. The climatic amelioration during Upper Magdalenian did not mean the recovery of camariña population in the Moraira headland area. Probably, the rising of the sea level would affect them destroying its dune habitat. Highlights: Palaeolithic groups from Cova de les Cendres gathered Corema album fruits. Corema album fruits are rich in vitamin C and they have a balanced mineral concentration. Corema album had larger Mediterranean populations during Upper Pleistocene. Late Glacial Maximum had a deep impact on Iberian vegetation dynamics.